ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENETAPAN UMK DI WILAYAH BARLINGMASCAKEB - Ghonimah Zumroatun Ainiyah; Dwi Adiyasha (Medikonis, 2020)
ABSTRACT The objective of this research was to find out the effect of Adequate Standard of Living (KHL), Consumer Price Index (IHK), and Gross Regional Domestic Product on the decision to determine regencies minimum wage (UMK) in Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen (Barlingmascakeb). The data were taken from the Indonesian Center for Statistics (BPS). This study used quantitative research. The data used in this research was secondary data. The population in this study was people from the Barlingmascakeb area with observational methods from 2010-2016. Saturated samples technique used in this research. Data analysis in this study used panel data regression analysis with SPSS 24 software. The result showed that based on regional panels, KHL partially has a positive and significant effect on the decision to determine regencies minimum wage in the Barlingmascakeb area. Whereas the IHK and PDRB have a negative and not significant effect on the decision to determine regencies minimum wage in the Barlingmascakeb area. Based on the time area, partially the KHL and PDRB have a positive and significant effect on the decision the determine regencies minimum wage in the Barlingmascakeb area. While IHK has a negative and not significant effect on the decision to determine regencies minimum wage in the Barlingmascakeb area.